Estimación de los costos indirectos de fabricación y su incidencia en el costo de producción de la empresa de embutidos Salinerito de la parroquia Salinas, provincia Bolívar, año 2023 - Manangón Fernández, Daniel Sebastián (2024)
The objective of this research is to estimate the indirect manufacturing costs and their impact on the cost of production at the Salinerito sausage factory, located in the Salinas Parish, Guaranda Canton, Bolivar Province, therefore, it is recognized that the factory has faced difficulties in the control and management of production costs. To support the research, a methodology based on situational analysis was used, which involved gathering information from both primary and secondary sources. Various techniques were used, including descriptive, documentary and field research. Descriptive research provided a general overview of the situation of the filling plant, while documentary research made it possible to analyze previous studies, regulations and historical data. In addition, field research was carried out through surveys and interviews, which provided direct and specific information on the perceptions and practices related to cost management.It is concluded that the research carried out on production costs at the "Salinerito" filling plant has provided an integral vision of the problem, identifying that the allocation of indirect costs should be prioritized.Therefore, the implementation of a production order costing system is suggested in order to determine the real costs of production, reduce waste and thus obtain better profitability and growth for the filler.